Identification of a novel RNA aptamer that selectively targets breast cancer exosomes - Carla Lucia Esposito; Cristina Quintavalle; Francesco Ingenito; Deborah Rotoli; Giuseppina Roscigno; Silvia Nuzzo; Renato Thomas; Silvia Catuogno; Vittorio de Franciscis; Gerolama Condorelli (Elsevier, 2021)
Breast cancer is a leading cause of cancer mortality in women. Despite advances in its management, the identification of new options for early-stage diagnosis and therapy of this tumor still represents a crucial challenge. Increasing evidence indicates that extracellular vesicles called exosomes may have great potential as early diagnostic biomarkers and regulators of many cancers, including breast cancer. Therefore, exploiting molecules able to selectively recognize them is of great interest. Here, we developed a novel differential SELEX strategy, called Exo-SELEX, to isolate nucleic acid aptamers against intact exosomes derived from primary breast cancer cells. Among the obtained sequences, we optimized a high-affinity aptamer (ex-50.T) able to specifically recognize exosomes from breast cancer cells or patient serum samples. Furthermore, we demonstrated that the ex.50.T is a functional inhibitor of exosome cellular uptake and antagonizes cancer exosome-induced cell migration in vitro. This molecule provides an innovative tool for the specific exosome detection and the development of new therapeutic approaches for breast cancer.